The little devil and the rose : lotería poems = El diablito y la rosa : poemas de la lotería - Canales, Viola (Arte Público Press, 2014)
A series of poems keyed to the cards in the traditional Mexican lottery game explore growing up Mexican-American in Texas, from enjoying afternoon snacks, climbing mesquite trees, and sharing Catholic traditions to enduring discrimination.